INVESTIGATION OF THE CAUSES OF YOUTH PIRACY BEHAVIOR IN LITHUANIA - Dambrava, Valdas; Grigūnas, Egidijus; Kozlovskij, Viktor; Rapkauskaitė, Ramunė; Vaitėnienė, Birutė (PROFESSIONAL STUDIES: Theory And Practice, 2023)
Digital piracy is a pervasive and persistent problem in the modern digital economy, with significant economic and social implications. The main aim of the paper is to find out the methods of analysis and factors of youth piracy behavior as well as investigate the main causes of youth piracy behavior in Lithuania. The objectives are to discuss theoretical models of consumer piracy behavior; to introduce the methodological background of the research; to investigate Lithuanian youth opinion and reasons of piracy behavior. An absolute majority of respondents find reasons to justify violation of author rights. The most popular reasoning is “why should one pay if it is possible to find anything free of charge on the internet?” and “it is too expensive to pay”. Having studied the problem from different aspects (by gender, place of residence, nature of activities), the results showed that there is no big difference between individual groups.